Energy storage electrode based on ferronickel bimetallic alkene nanometer material and preparation method thereof
The preparation of nickel-ferrobimetalene nanomaterials by hydrothermal method solves the problems of low conductivity and poor cycle stability of energy storage electrode materials, and realizes the preparation of high-performance energy storage electrodes, which has high energy storage and good cycle stability. The process is simple and the cost is low, and it is suitable for industrial promotion.
Patent Information
- Application Number
- CN202411358297.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-20
AI Technical Summary
The low conductivity and poor cycle stability of existing energy storage electrode materials limit their application potential in the field of supercapacitors.
The hydrothermal method is used to prepare nickel-ferrobimetalene nanomaterials, and the nickel-ferrobimetalene nanomaterials with a unique layered structure are obtained through magnetic stirring and autoclave reduction reaction, and mixed with acetylene black and polytetrafluoroethylene to spray to foam. The nickel substrate was dried and pressed to prepare a high-performance energy storage electrode.
It achieves high energy storage capacity and good cycle stability, and is simple in process and low in cost, making it suitable for industrial applications.
Smart Images

Figure CN119170426A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an energy storage electrode based on nickel-iron bimetallic olefin nanomaterial and a preparation method thereof, belonging to the technical field of energy storage electrodes. Background Art
[0002] In recent years, with the increasing demand for energy and the urgent need for the development of sustainable energy technologies and equipment, supercapacitors, as the basic electrochemical storage technology in renewable energy, can effectively narrow the gap between batteries and traditional capacitors. A lot of research has been done on carbon materials, transition metal oxides, transition metal sulfides and their composite electrode materials to explore their potential application value in the field of supercapacitors. However, these materials still have certain limitations, and their actual specific capacity is much lower than the theoretical value. The low electrical conductivity and poor cycle stability of electrode materials limit their application in the field of energy storage. Summary of the invention
[0003] The purpose of the present invention is to overcome the deficiencies in the prior art and provide an energy storage electrode based on nickel-iron bimetallic olefin nanomaterials and a preparation method thereof. The nickel-iron bimetallic olefin nanomaterials prepared by a hydrothermal method have a unique layered structure, and the energy storage electrode prepared based on this exhibits higher energy storage capacity and better cycle stability.
[0004] To achieve the above object, the present invention is implemented by adopting the following technical solutions: On the one hand, the present invention discloses a method for preparing an energy storage electrode based on nickel-iron bimetallic olefin nanomaterial, comprising the following steps: dissolving a nickel source in a formaldehyde solution to obtain a first solution; dissolving an iron source in a formaldehyde solution to obtain a second solution; transferring the second solution into the first solution, and obtaining a third solution after magnetic stirring; The third solution is poured into an autoclave for reduction reaction, cooled to room temperature, taken out, and washed and dried to obtain a nickel-iron bimetallic olefin nanomaterial; The nickel-iron bimetallic olefin nanomaterial is mixed with acetylene black and polytetrafluoroethylene, and then anhydrous ethanol is added and stirred evenly to obtain a dispersion; The dispersion is sprayed onto a foamed nickel substrate, and subjected to drying and pressing processes to obtain an energy storage electrode.
[0005] Furthermore, the nickel source includes nickelous chloride, and the concentration of the nickel source in the first solution is 20.5-30.8 mmol / L.
[0006] Furthermore, the iron source includes anhydrous ferrous chloride, and the concentration of the iron source in the second solution is 13.1-52.5 mmol / L.
[0007] Further, obtaining the third solution comprises: The second solution is transferred to the first solution, and magnetic stirring is performed for 4-6 hours to obtain a third solution, wherein the molar ratio of the nickel source to the iron source in the third solution is in the range of 0.58-1.56.
[0008] Furthermore, in the reduction reaction, the autoclave is a stainless steel autoclave lined with polytetrafluoroethylene; the reaction temperature is set at 160-200°C, and the duration is 10-12 h.
[0009] Furthermore, the drying process is carried out at a temperature of 50-70°C and lasts for 10-12 hours.
[0010] Furthermore, the mixing mass ratio of the nickel-iron bimetallic olefin nanomaterial to acetylene black and polytetrafluoroethylene is 80:15:5; the volume of the anhydrous ethanol is 50-100 mL, and the concentration of the dispersion is 98.9 wt%.
[0011] Furthermore, the drying treatment adopts vacuum drying, the drying temperature is 55-65°C, and the drying time is 22-26h.
[0012] Furthermore, during the compression process, the pressure of the tablet press is 10 MPa and the tablet compression time is 10-12 h.
[0013] On the other hand, the present invention discloses an energy storage electrode based on nickel-iron bimetallic olefin nanomaterials, which is prepared by the above-mentioned method for preparing an energy storage electrode based on nickel-iron bimetallic olefin nanomaterials.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the energy storage electrode based on nickel-iron bimetallic olefin nanomaterial of the present invention, first, the nickel-iron bimetallic olefin nanomaterial prepared by the hydrothermal method has a unique layered structure and can achieve different atomic structure ratios. Secondly, compared with the current traditional energy storage electrodes, the energy storage electrode based on nickel-iron bimetallic olefin nanomaterials exhibits higher energy storage capacity and better cycle stability. Finally, the preparation process of the method is simple, easy to operate and low in cost, which is conducive to industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a flow chart of a method for preparing an energy storage electrode based on nickel-iron bimetallic olefin nanomaterials provided in an embodiment; Figure 2 is a field emission scanning electron microscope image of the nickel-iron bimetallic olefin nanomaterial provided in Example 3; Figure 3 is a transmission electron microscope image of the energy storage electrode provided in Example 3; Figure 4 It is an electrochemical CV energy storage test diagram of the energy storage electrode with different addition amounts of anhydrous ferrous chloride provided in Examples 1-4; Figure 5 It is a schematic diagram of the cyclic stability test of the energy storage electrode provided in Example 3. DETAILED DESCRIPTION
[0016] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0017] This embodiment provides a method for preparing an energy storage electrode based on nickel-iron bimetallic olefin nanomaterial, comprising the following steps: dissolving a nickel source in a formaldehyde solution to obtain a first solution; dissolving an iron source in a formaldehyde solution to obtain a second solution; The second solution is transferred into the first solution, and a third solution is obtained after magnetic stirring; The third solution is poured into an autoclave for reduction reaction, then taken out after cooling to room temperature, and washed and dried to obtain a nickel-iron bimetallic olefin nanomaterial; The nickel-iron bimetallic olefin nanomaterial is mixed with acetylene black and polytetrafluoroethylene, and then anhydrous ethanol is added and stirred evenly to obtain a dispersion; The dispersion is sprayed onto a nickel foam substrate, and an energy storage electrode is obtained through drying and pressing.
[0018] The technical concept of the present invention is as follows: First, the nickel-iron bimetallic olefin nanomaterial prepared by the hydrothermal method has a unique layered structure and can achieve different atomic structure ratios. Secondly, compared with the current traditional energy storage electrodes, the energy storage electrode based on the nickel-iron bimetallic olefin nanomaterial exhibits higher energy storage capacity and better cycle stability. Finally, the preparation process of this method is simple, easy to operate and low in cost, which is conducive to industrial promotion and application.
[0019] The nickel source in the method includes nickelous chloride, and the concentration of the nickel source in the first solution is 30.8 mmol / L; the mass fraction of the formaldehyde solution is 37 wt%. The iron source includes anhydrous ferrous chloride, and the concentration of the iron source in the second solution is 39.4 mmol / L. The molar ratio of the nickel source to the iron source in the third solution is between 0.58 and 1.56.
[0020] like Figure 1 As shown, the specific preparation steps are as follows: (1) Dissolve 80-120 mg of anhydrous nickelous chloride in 30 mL of formaldehyde solution and stir magnetically for 30-60 min to prepare a uniform first solution.
[0021] In this embodiment, the preferred amount of anhydrous nickelous chloride is 100 mg. The mass fraction of the formaldehyde solution is 37 wt%.
[0022] (2) Dissolve 50-200 mg of anhydrous ferrous chloride in 30 mL of formaldehyde solution and stir magnetically for 30-60 min to prepare a uniform second solution.
[0023] The anhydrous nickelous chloride in this embodiment is 50 mg, 100 mg, 150 mg and 200 mg respectively, and the mass fraction of the formaldehyde solution is 37 wt %.
[0024] (3) The second solution is transferred into the first solution and magnetically stirred for 4-6 h to obtain the third solution.
[0025] (4) The third solution is poured into an autoclave for reduction reaction, and then taken out after cooling to room temperature. After washing and drying, a nickel-iron bimetallic olefin nanomaterial is obtained.
[0026] In the reduction reaction, in order to provide a sufficient reducing environment, the autoclave used a 100 mL polytetrafluoroethylene-lined stainless steel autoclave; the reaction temperature was set at 160-200 °C, and the duration was 10-12 h.
[0027] The drying temperature is 50-70 ℃ and the duration is 10-12 hours.
[0028] Specifically, the third solution was poured into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, the reaction temperature was set at 180 °C, and the duration was 12 h to obtain a sample. After the sample was naturally cooled to room temperature, it was washed three times with deionized water and anhydrous ethanol respectively, and then transferred to a vacuum oven for drying at 60 °C for 12 h.
[0029] (5) The prepared nickel-iron bimetallic olefin nanomaterial is mixed with acetylene black and polytetrafluoroethylene in a ratio of 80:15:5, 50-100 mL of anhydrous ethanol is added, and the solution is evenly dispersed by ultrasound to prepare a dispersion of a certain concentration.
[0030] The volume of anhydrous ethanol in this example is 80 mL, and the concentration of the dispersion is 98.9 wt %.
[0031] (6) The dispersion is sprayed onto a nickel foam substrate, and after drying and pressing, an energy storage electrode is obtained.
[0032] The drying process adopts vacuum drying, the drying temperature is 55-65 ℃, and the drying time is 22-26 hours. In the compression process, the pressure of the tablet press is 10 MPa, and the tablet pressing time is 10-12 hours.
[0033] Specifically, in this embodiment, a commercial electrostatic spray system is used to spray the dispersion onto a 1 cm×1 cm nickel foam substrate, and vacuum dried at 60°C for 24 h to obtain a working electrode. Subsequently, a powder tablet press is used at a pressure of 10 MPa for 12 h to press the working electrode into a thin sheet to obtain an energy storage electrode.
[0034] The mass of active material was calculated by weighing the mass of nickel foam before and after, and the mass of active material was 0.107 g. Example 1
[0035] In this embodiment 1, the preparation method of the energy storage electrode based on the nickel-iron bimetallic olefin nanomaterial prepared the energy storage electrode NiFe-1 with an addition amount of 50 mg of anhydrous ferrous chloride, as follows: (1) Dissolve 100 mg of anhydrous nickelous chloride in 30 mL of formaldehyde solution and stir magnetically for 45 min to prepare a uniform first solution.
[0036] (2) Dissolve 50 mg of anhydrous ferrous chloride in 30 mL of formaldehyde solution and stir magnetically for 45 min to prepare a uniform second solution.
[0037] (3) The second solution was transferred into the first solution and magnetically stirred for 6 h to obtain the third solution.
[0038] (4) Pour the third solution into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, set the reaction temperature at 180°C, and last for 12 h to obtain a sample. After the sample is cooled to room temperature naturally, it is washed three times with deionized water and anhydrous ethanol respectively, and then transferred to a vacuum oven for drying at 60°C for 12 h.
[0039] (5) The prepared nickel-iron bimetallic olefin nanomaterial was mixed with acetylene black and polytetrafluoroethylene in a ratio of 80:15:5, 80 mL of anhydrous ethanol was added, and the solution was evenly dispersed by ultrasonication to prepare a dispersion with a concentration of 98.9 wt%.
[0040] (6) The dispersion was sprayed onto a 1 cm × 1 cm nickel foam substrate and vacuum dried at 60 °C for 24 h to obtain a working electrode. The working electrode was then pressed into a thin sheet using a powder press at a pressure of 10 MPa for 12 h to obtain the energy storage electrode NiFe-1. Example 2
[0041] In this embodiment 2, the preparation method of the energy storage electrode based on the nickel-iron bimetallic olefin nanomaterial prepared the energy storage electrode NiFe-2 with an addition amount of 100 mg of anhydrous ferrous chloride, as follows: (1) Dissolve 100 mg of anhydrous nickelous chloride in 30 mL of formaldehyde solution and stir magnetically for 45 min to prepare a uniform first solution.
[0042] (2) Dissolve 100 mg of anhydrous ferrous chloride in 30 mL of formaldehyde solution and stir magnetically for 45 min to prepare a uniform second solution.
[0043] (3) The second solution was transferred into the first solution and magnetically stirred for 6 h to obtain the third solution.
[0044] (4) Pour the third solution into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, set the reaction temperature at 180°C, and last for 12 h to obtain a sample. After the sample is cooled to room temperature naturally, it is washed three times with deionized water and anhydrous ethanol respectively, and then transferred to a vacuum oven for drying at 60°C for 12 h.
[0045] (5) The prepared nickel-iron bimetallic olefin nanomaterial was mixed with acetylene black and polytetrafluoroethylene in a ratio of 80:15:5, 80 mL of anhydrous ethanol was added, and the solution was evenly dispersed by ultrasonication to prepare a dispersion with a concentration of 98.9 wt%.
[0046] (6) The dispersion was sprayed onto a 1 cm × 1 cm nickel foam substrate and vacuum dried at 60 °C for 24 h to obtain a working electrode. The working electrode was then pressed into a thin sheet using a powder press at a pressure of 10 MPa for 12 h to obtain the energy storage electrode NiFe-2. Example 3
[0047] In this embodiment 3, the preparation method of the energy storage electrode based on nickel-iron bimetallic olefin nanomaterials prepared an energy storage electrode NiFe-3 with an addition amount of 150 mg of anhydrous ferrous chloride, as follows: (1) Dissolve 100 mg of anhydrous nickelous chloride in 30 mL of formaldehyde solution and stir magnetically for 45 min to prepare a uniform first solution.
[0048] (2) Dissolve 150 mg of anhydrous ferrous chloride in 30 mL of formaldehyde solution and stir magnetically for 45 min to prepare a uniform second solution.
[0049] (3) The second solution was transferred into the first solution and magnetically stirred for 6 h to obtain the third solution.
[0050] (4) Pour the third solution into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, set the reaction temperature at 180°C, and last for 12 h to obtain a sample. After the sample is cooled to room temperature naturally, it is washed three times with deionized water and anhydrous ethanol respectively, and then transferred to a vacuum oven for drying at 60°C for 12 h.
[0051] (5) The prepared nickel-iron bimetallic olefin nanomaterial was mixed with acetylene black and polytetrafluoroethylene in a ratio of 80:15:5, 80 mL of anhydrous ethanol was added, and the solution was evenly dispersed by ultrasonication to prepare a dispersion with a concentration of 98.9 wt%.
[0052] (6) The dispersion was sprayed onto a 1 cm × 1 cm nickel foam substrate and vacuum dried at 60 °C for 24 h to obtain a working electrode. The working electrode was then pressed into a thin sheet using a powder press at a pressure of 10 MPa for 12 h to obtain the energy storage electrode NiFe-3. Example 4
[0053] In this embodiment 4, the preparation method of the energy storage electrode based on the nickel-iron bimetallic olefin nanomaterial prepared the energy storage electrode NiFe-4 with an addition amount of 200 mg of anhydrous ferrous chloride, as follows: (1) Dissolve 100 mg of anhydrous nickelous chloride in 30 mL of formaldehyde solution and stir magnetically for 45 min to prepare a uniform first solution.
[0054] (2) Dissolve 200 mg of anhydrous ferrous chloride in 30 mL of formaldehyde solution and stir magnetically for 45 min to prepare a uniform second solution.
[0055] (3) The second solution was transferred into the first solution and magnetically stirred for 6 h to obtain the third solution.
[0056] (4) Pour the third solution into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, set the reaction temperature at 180°C, and last for 12 h to obtain a sample. After the sample is cooled to room temperature naturally, it is washed three times with deionized water and anhydrous ethanol respectively, and then transferred to a vacuum oven for drying at 60°C for 12 h.
[0057] (5) The prepared nickel-iron bimetallic olefin nanomaterial was mixed with acetylene black and polytetrafluoroethylene in a ratio of 80:15:5, 80 mL of anhydrous ethanol was added, and the solution was evenly dispersed by ultrasonication to prepare a dispersion with a concentration of 98.9 wt%.
[0058] (6) The dispersion was sprayed onto a 1 cm × 1 cm nickel foam substrate and vacuum dried at 60 °C for 24 h to obtain a working electrode. The working electrode was then pressed into a thin sheet using a powder press at a pressure of 10 MPa for 12 h to obtain the energy storage electrode NiFe-4.
[0059] like Figure 4 As shown, the energy storage electrodes prepared in Examples 1-4 were subjected to electrochemical CV tests using a three-electrode electrochemical workstation, with a scanning frequency of 10 mV / s. In comparison, when the amount of anhydrous ferrous chloride FeCl2 added to the nickel-iron bimetallic olefin nanomaterial was 150 mg, its electrochemical CV area was the largest, and this energy storage electrode material exhibited a higher energy storage ability.
[0060] like Figure 2 As shown, the field emission scanning electron microscope photo of the nickel-iron bimetallic olefin nanomaterial when the addition amount of anhydrous ferrous chloride FeCl2 in Example 3 is 150 mg, it can be seen that the nickel-iron bimetallic olefin nanomaterial reacts and assembles into a nanoflower-like structure in the reactor, which has a typical sheet structure.
[0061] like Figure 3 As shown in the transmission electron microscope photo of the energy storage electrode when the addition amount of anhydrous ferrous chloride FeCl2 in Example 3 is 150 mg, it shows a highly transparent thin-sheet posture, proving that the prepared energy storage electrode is a thin-sheet structure, and also shows a layered sample morphology. Figure 5 As shown, a cycle stability test was carried out on the energy storage electrode with an addition amount of 150 mg of anhydrous ferrous chloride FeCl2, which showed good cycle stability.
[0062] For the energy storage electrode of Example 3 with an addition amount of 150 mg of anhydrous ferrous chloride FeCl2, a stability test was further conducted with existing electrode materials, as shown in the following table.
[0063]
[0064] It can be seen that compared with existing electrodes, the specific capacitance and cycle stability of the energy storage electrode of the present invention used in the field of supercapacitors are significantly improved.
[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an energy storage electrode based on nickel-iron bimetallic olefin nanomaterial, characterized in that: The following steps are involved: dissolving a nickel source in a formaldehyde solution to obtain a first solution; dissolving an iron source in a formaldehyde solution to obtain a second solution; transferring the second solution into the first solution to obtain a third solution; The third solution is poured into an autoclave for reduction reaction, cooled to room temperature, taken out, and washed and dried to obtain a nickel-iron bimetallic olefin nanomaterial; The nickel-iron bimetallic olefin nanomaterial is mixed with acetylene black and polytetrafluoroethylene, and then anhydrous ethanol is added and stirred evenly to obtain a dispersion; The dispersion is sprayed onto a foamed nickel substrate, and subjected to drying and pressing processes to obtain an energy storage electrode.
2. The method for preparing the energy storage electrode based on nickel-iron bimetallic olefin nanomaterial according to claim 1, characterized in that: The nickel source includes nickelous chloride, and the concentration of the nickel source in the first solution is 20.5-30.8 mmol / L.
3. The method for preparing the energy storage electrode based on nickel-iron bimetallic olefin nanomaterial according to claim 1, characterized in that: The iron source includes anhydrous ferrous chloride, and the concentration of the iron source in the second solution is 13.1-52.5 mmol / L.
4. The method for preparing the energy storage electrode based on nickel-iron bimetallic olefin nanomaterial according to claim 1, characterized in that: The obtaining of the third solution comprises: The second solution is transferred to the first solution, and magnetic stirring is performed for 4-6 hours to obtain a third solution, wherein the molar ratio of the nickel source to the iron source in the third solution is in the range of 0.58-1.
56.
5. The method for preparing the energy storage electrode based on nickel-iron bimetallic olefin nanomaterial according to claim 1, characterized in that: In the reduction reaction, the autoclave is a stainless steel autoclave lined with polytetrafluoroethylene; the reaction temperature is set at 160-200°C, and the duration is 10-12 hours.
6. The method for preparing the energy storage electrode based on nickel-iron bimetallic olefin nanomaterial according to claim 1, characterized in that: The drying process is carried out at a temperature of 50-70°C and lasts for 10-12 hours.
7. The method for preparing the energy storage electrode based on nickel-iron bimetallic olefin nanomaterial according to claim 1, characterized in that: The mixing mass ratio of the nickel-iron bimetallic olefin nanomaterial to acetylene black and polytetrafluoroethylene is 80:15:5; the volume of the anhydrous ethanol is 50-100 mL, and the concentration of the dispersion is 98.9 wt%.
8. The method for preparing the energy storage electrode based on nickel-iron bimetallic olefin nanomaterial according to claim 1, characterized in that: The drying process adopts vacuum drying, the drying temperature is 55-65°C, and the drying time is 22-26 hours.
9. The method for preparing the energy storage electrode based on nickel-iron bimetallic olefin nanomaterial according to claim 1, characterized in that: During the compression process, the tablet press pressure is 10 MPa and the tablet compression time is 10-12 h.
10. An energy storage electrode based on nickel-iron bimetallic olefin nanomaterial, characterized in that: The energy storage electrode based on nickel-iron bimetallic olefin nanomaterial is prepared by the preparation method of the energy storage electrode based on nickel-iron bimetallic olefin nanomaterial as described in any one of claims 1 to 9.
